Treatment of ADHD: Guanfacine Extended Release in ADHD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Massachusetts General Hospital, Boston, MA, performed a multicenter, 9-week, double-blind, placebo-controlled, dose-optimization study of guanfacine extended release (GXR, <4 mg/d) adjunctive to a long-acting psychostimulant for ADHD continued in 461 subjects.